The evaluation of practical and interdisciplinary teaching sequence for teaching the importance of pH in food preservation (Research, Society and Development, 2020)
The complexity of contemporary professional practice motivates teaching in professional and technological education to find ways of curricular integration aimed at meeting the principles of human development in the full sense. Therefore, the present work aimed to evaluate interdisciplinary didactic sequence with practical experiments based on problem-based learning in order to construct knowledge of the influence of pH on food conservation, within the Federal Network of Professional and Technological Education. The didactic sequence was developed by using practical activities with alternative materials and commonly used equipment in food laboratories. The proposal was evaluated by applying a questionnaire to 10 chemistry teachers (Basic Curriculum) and the food production axis of Federal Institutes in five regions of Brazil. The results showed that 100% of the participating teachers were interested in applying the didactic sequence proposed. Although some institutions have infrastructure limitations, the evaluation carried out in this study confirmed the feasibility of applying the didactic sequence developed in the courses of the Federal Network of Professional and Technological Education.